Limiting and excreting metabolites of succinate production in s.cerevisiae using flux balance analysis - Nurhafiza Rosdi, 1991-, author 604985; Afnizanfaizal Abdullah, 1985-, supervisor 485493; Fakulti Komputeran 538688 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Sains Komputer (Bioinformatik)) - Universiti Teknologi Malaysia, 2014